2022
DOI: 10.51630/ijes.v3i1.37
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fly Ash Utilization in Reinforcement Concrete: A Review

Abstract: Indonesia signed the Paris Agreement on facing climate change. Carbon dioxide is the main issue contributing to the greenhouse effect. Most power plant in Indonesia uses non-renewable energy to generate electricity. Increasing demand for electricity makes increasing coal consumption for steam power plants and directly contributes to greenhouse gasses from coal combustion and produces fly ash as a waste product. Otherwise, fly ash from Steam Power Plant is classified as pozzolanic materials being a part of subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The smaller the double-layer capacitance (Cdl) value, the higher the thickness. This can cause a decrease in the corrosion rate due to the adsorption of coating molecules on the metal surface, thereby preventing direct contact with aggressive solution molecules [20]. The results showed that the four specimens had very low CPE values within the range of 1.15E-03 F to 8.48E-05 F.…”
Section: Electrochemical Impedance Spectroscopy (Eis) Testingmentioning
confidence: 99%
“…The smaller the double-layer capacitance (Cdl) value, the higher the thickness. This can cause a decrease in the corrosion rate due to the adsorption of coating molecules on the metal surface, thereby preventing direct contact with aggressive solution molecules [20]. The results showed that the four specimens had very low CPE values within the range of 1.15E-03 F to 8.48E-05 F.…”
Section: Electrochemical Impedance Spectroscopy (Eis) Testingmentioning
confidence: 99%
“…In the building industry, the CaCO3/Fly-Ash composite is used for precast concrete, concrete pavements, and concrete blocks, and, lastly, it is a workable alternative to traditional concrete. [7,8]. It can also be implemented in soil stabilisation initiatives to enhance the soil's load-bearing capacity [9].…”
Section: Introductionmentioning
confidence: 99%